Sodium bicarbonate supplementation in resistance exercise performance, perceived exertion and blood lactate concentration - Letícia Rodrigues Fontanella; Cíntia Azara; Estevão Scudese; Diogo de Oliveira Silva; Carlos José Nogueira; Michelle Soraia Espínola Costa; Gilmar Weber Senna (Universidade Estadual Paulista (UNESP), 2020)
Abstract Aim: The aim was to evaluate the effect of sodium bicarbonate supplementation (NaHCO3) in repetition performance, perceived exertion and blood lactate concentration. Methods: Fourteen trained men (25.14 ± 3.5 years; 85.83 ± 10.18 kg; 1.78 ± 0.06 m; 26.88 ± 3.17 kg/m2) realized two upper-body resistance exercise sessions consisting of 15-RM load and 1 minute of the interval, combining bicarbonate supplementation (BS) or Placebo conditions. Results: After the ANOVA analysis, no difference was found on the total number of repetitions during the session on both BS and Placebo condition (p = 0.11). However, a greater number of total of repetitions on the machine chest fly exercise for BS vs. Placebo condition (p = 0.04) was observed. The perceived exertion increased regardless of the supplementation condition (p < 0.0001). Additionally, for the blood lactate was observed significant increases in BS vs. Placebo condition in the post verification (p = 0.013), corroborated for a bigger area under the curve (AUC) on the BS compared to Placebo (p = 0.026) condition. Conclusion: In conclusion, sodium bicarbonate supplementation was not able to improve performance during a resistance exercise session, except for the single-joint exercise performed with high values of perceived exertion, not altering the perceived exertion, and blood lactate between protocols.